Primary care nurses' knowledge of palliative care, attitude towards caring for dying patients, and their relationship with evidence-based practice - Alexandra Masharipova; Nassikhat Nurgaliyeva; Gulmira Derbissalina (Tehran University of Medical Sciences, 2024)
Background & Aim: Palliative care is an approach designed for critically ill patients, improving their quality of life and alleviating suffering through early detection, proper assessment, and treatment of pain and other problems, whether physical, psychosocial, or spiritual. The purpose of this study was to assess nurses' knowledge of palliative care and attitudes toward caring for dying patients and their relationship with evidence-based practice. Methods & Materials: A cross-sectional study design was employed to collect data from 565 nurses working in primary healthcare organizations from January 2022 to March 2023. An online questionnaire included four parts: demographic and professional characteristics, PCQN, FATCOD, and EBPQ questionnaires. An independent T-test, One-Way ANOVA, and Kendall tau rank correlation coefficient, hierarchical multiple regression were performed. Results: Nurses' palliative care knowledge level was low (mean score: 9.06±2.93). The majority of nurses (93%) have a neutral or negative attitude toward caring for dying patients (94.50±12.41). The obtained score (4.39 ±1.05) on the EBPQ scale indicates an average level of competence in evidence-based practice. Work experience (β=0.534; <0.001) and competencies in evidence-based practice (β=0.136; p=0.001) are statistically significant factors that affect knowledge of palliative care. The aspect of Knowledge/skills in EBP is the most significant (β=0.122; p=0.005). Conclusion: An insufficient level of nurses' knowledge about palliative care and a neutral or negative attitude towards caring for dying patients were revealed. The results also indicate that much attention and resources should be directed toward improving the level of knowledge of nurses in the field of evidence-based practice.